Biotransformation of ginsenosides Rb1 by bacterial crude enzyme of Paenibacillus spp. strain E3 isolated from Vietnamese ginseng soil - Tran, Tram Bao (Academia Journal of Biology, 2018)
In ginseng, minor ginsenosides were more effective pharmacological properties than major ginsenosides. Therefore, finding bacteria that can convert major ginsenosides has been paying attention. Ginsenoside Rb1 is one of major ginsenosides of ginseng and its biotransformation produces pharmacologically active compounds such as compound K. In this study, the isolation of bacterial strains from Vietnamese ginseng cultivated soil was carried out with the objective of evaluating their hydrolytic capacity for use in biotransformation of ginsenosides Rb1. In the screening of β-glucosidase producing bacteria, seven isolates exhibited black color zones on R2A agar medium containing esculine. Among seven isolates, strain E3 showed the highest ability biotransformation of ginsenosides Rb1 in Luria-Bertani broth. Therefore, strain E3 was selected for further research. Biotransformation of Rb1 was observed by using thin layer chromatography (TLC) and high performance liquid chromatography (HPLC) with ginsenoside standards for comparison. We determined the optimal conditions for biotransformation of ginsenoside Rb1 into the compound K of crude enzymes of strain E3 were at 30°C, pH 7,0 and 3 days. Ginsenoside Rb1 was converted into compound K via ginsenoside Rd and F2. The analyses of 16S rRNA gene and phylogenetic tree indicated that strain E3 was closely related to Paenibacillus terrigena with 99,4% identity and formed a discrete cluster with type strain Paenibacillus terrigena A35T with high bootstrap support (99%), supporting strain E3 belonging to the species Paenibacillus terrigena. Physiological characteristics also supported strain E3 belonging to the genus Peanibacillus. This is the first report of biotransformation of ginsenosides using bacterial strains isolated from Vietnamese ginseng cultivated soil in Vietnam. Based on our the obtained results, strain E3 could be applied for the preparation of ginsenoside compound K for use in the cosmetic and pharmaceutical industries. :